Bipolar transurethral enucleation and resection of the prostate versus bipolar resection of the prostate for prostates larger than 60gr: A retrospective study at a single academic tertiary care center - Wei,Yong (2016)
ABSTRACT Objective: To evaluate the efficacy and safety of bipolar transurethral enucleation and resection of the prostate (B-TUERP) versus bipolar transurethral resection of the prostate (B-TURP) in the treatment of prostates larger than 60g. Material and Methods: Clinical data for 270 BPH patients who underwent B-TUERP and 204 patients who underwent B-TURP for BPH from May 2007 to May 2013 at our center were retrospectively analyzed. Outcome measures included operative time, decreased hemoglobin level, total prostate specific antigen (TPSA), International Prostate Symptom Score (IPSS), maximal urinary flow rate (Qmax), quality of life (QoL) score, post void residual urine volume (RUV), bladder irrigation duration, hospital stay, and the weight of resected prostatic tissue. Other measures included perioperative complications including transurethral resection syndrome (TURS), hyponatremia, blood transfusion, bleeding requiring surgery, postoperative acute urinary retention, urine incontinence and urinary sepsis. Patients in both groups were followed for two years. Results: Compared with the B-TURP group, the B-TUERP group had shorter operative time, postoperative bladder irrigation duration and hospital stay, a greater amount of resected prostatic tissue, less postoperative hemoglobin decrease, better postoperative IPSS and Qmax, as well as lower incidences of hyponatremia, urinary sepsis, blood transfusion requirement, urine incontinence and reoperation (P<0.05 for all). Conclusions: B-TUERP is superior to B-TURP in the management of large volume BPH in terms of efficacy and safety, but this finding needs to be validated in further prospective, randomized, controlled studies.